PENGARUH PIJAT BAYI MENGGUNAKAN KANDUNGAN MINYAK KELAPA TERHADAP PENINGKATAN BERAT BADAN BAYI USIA 4– 6 BULAN DI PUSKESMAS PAKUAN RATU: Efect Of Baby Massage Using Coconut Oil Content On Weight Increasing Body Of Infants Aged 4– 6 Months At Puskesmas Pakuan Ratu 2022 - Hermawati, Iluh Dewi Hermawati (LPPM - STIKES Pemkab Jombang, 2023)
Efforts that can be made in optimizing the baby's weight in addition to the nutrition provided by the mother and one other way are the need for stimulation or what is commonly known as baby massage. Baby massage using coconut oil (VCO) is a stimulation that is beneficial in increasing nutritional intake and is also beneficial for mothers in increasing confidence in caring for their babies VCO contains MCFA which can increase body weight. The purpose of this study was to determine the effect of infant massage using coconut oil content on increasing the weight of infants aged 4-6 months at the Pakuan Ratu Health Center. This study uses a research method that is experimental with a pre-experimental approach (one group pretest posttest). Based on the total sampling technique obtained a total sample of 44 respondents. The research results show; 1). Most of those who visited the Pakuan Ratu Health Center in Kab. Way Kanan was female, with 24 babies (54.5%), 2). Most of those who visited the Pakuan Ratu Health Center in Kab. Way Kanan was 5 months old with 16 babies (36.4%). 3). The weight of infants aged 4-6 months at the Pakuan Ratu Health Center before being massaged using coconut oil was 6,000-7,000 grams in 19 children (43.2%). 4). The weight of babies aged 4-6 months at the Pakuan Ratu Health Center after being massaged using coconut oil was in part 0.001-8.000 grams as many as 17 children (38.6%). 5). 4– 6 months at the Pakuan Ratu Health Center, Kab. Right Way (p value 0.000 <0.05). The community should pay more attention to the growth and development of their babies both in terms of fulfilling nutrition, environmental hygiene and parenting patterns for babies to maximize the growth and development of babies, especially in increasing the baby's weight by providing stimulation to the baby.